DEVELOPING STUDENTS’ SPEECH SKILLS THROUGH STORYTELLING TECHNOLOGY - Khamroyeva Guzal Khuroz qizi (Web of Journals Publishing, 2026)
In modern teacher education, developing students’ speech competence is considered a key professional requirement. This article explores the pedagogical potential of storytelling technology in developing the speech skills of primary education students. The study analyzes the role of storytelling as an innovative instructional approach in the course “Methods of Speech Development” and its impact on students’ oral communication, communicative competence, creative thinking, and professional speech culture. The research findings indicate that storytelling technology enhances students’ speech activity, confidence, and ability to express ideas logically and fluently. The article concludes that systematic integration of storytelling technology into teacher education programs contributes significantly to preparing future primary school teachers in accordance with contemporary educational standards.
Keywords: Storytelling technology, speech development, communicative competence, primary education students, innovative teaching methods.